As the crow flies - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery., 2012)
When the site of his daughter's upcoming wedding burns down, Wyoming Sheriff Walt Longmire and his friend, Henry Standing Bear, witness the falling death of a young Crow woman and are recruited into an investigation that incites the wrath of the bride-to-be.